The Development of QR Code-Based Arabic Textbooks for Non-Arabic Education Students - Nadziro, Maslahatun; Aisa, Aufia; Rahmawati, Rina Dian (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to design a QR Code-Based Arabic Textbook and determine its effectiveness. This research is a Research and Development (R&D) with the Borg and Gall development model. Data collection techniques using observation, interviews, tests, and questionnaires. Primary data sources are Arabic vocabulary teaching materials for 2nd-semester management students, lecturers teaching Arabic courses, and 2nd-semester management students, while the primary data source is related articles. The population in this study were all 36 semester two management students, with a sample of 2 semester two management study program students. As for the sampling technique using purposive sampling. Data analysis technique using the Wilcoxon test. The results showed that students were interested in using QR Code-based Arabic Textbooks, which could increase Arabic vocabulary, especially second-semester students of the management study program University of KH. A. Wahab Hasbullah Jombang. The effectiveness of textbooks is obtained through the results of the Wilcoxon Test; it is known as the Asymp Sig value. (2-tailed) is 0.000 <0.05, which means that Ha is accepted; that is, there is a significant difference in the learning outcomes of the second-semester students of the management study program at University KH. A. Wahab Hasbullah Jombang. Thus, developing textbooks with QR Code innovations can improve student learning outcomes in the second semester of the management study program at University KH. A. Wahab Hasbullah Jombang in adding Arabic vocabulary.